Correlation between landscape structure and distribution of Javan Pangolin (Manis javanica) in an extreme landscape - SUSANTI WITHANINGSIH; Parikesit PARIKESIT; ANWAR NASRUDIN (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Withaningsih S, Parikesit, Nasrudin A. 2021. Correlation between landscape structure and distribution of Javan Pangolin (Manis javanica) in an extreme landscape. Biodiversitas 22: 920-932. The Javan Pangolin (Manis javanica) is a unique mammal with hard scales and can roll over when threatened. However, the study of Javan pangolin ecology, particularly using an ecological landscape approach, is limited. Here, a spatial analysis of the presence and distribution of Javan pangolins living in an extreme landscape in Rongga Sub-district, West Bandung District was conducted and was correlated to the landscape structure using a landscape metric approach. A descriptive method was used in conjunction with quantitative statistical analyses using simple linear regressions based on the Pearson correlation coefficient. The variables were features of the extreme landscape structure and the number of Javan pangolin animal signs at the sampling sites. The seven sample sites had variations in land cover classes, and the landscape structure affected the distribution of the Javan pangolins. The pangolin distribution showed a strong, negative correlation with the number of patch types (R2 = 0.628) and a weak, negative correlation with both the landscape heterogeneity (R2 = 0.012) and the percentage of forest cover (R2 = 0.136). Together, the landscape heterogeneity, the number of patch types and the percentage of forest cover negatively affected the distribution of Javan pangolins, showing a strong correlation (R2 = 0.799).